Impact of emergency department care on outcomes of acute pain events in children with sickle cell disease. Issue 12 (3rd September 2016) - Brandow, Amanda M.; Nimmer, Mark; Simmons, Timothy; Charles Casper, T.; Cook, Lawrence J.; Chumpitazi, Corrie E.; Paul Scott, J.; Panepinto, Julie A.; Brousseau, David C.
Abstract : The impact of emergency department (ED) treatment on outcomes of sickle cell disease (SCD) acute pain hospitalizations is not well described. We investigated whether length of stay (LOS) and change in health‐related quality of life (HRQL) are affected by initial opioid dose and time to administration. We conducted secondary analyses of data from the randomized‐controlled Magnesium for children in Crisis (MAGiC) trial. The primary outcome was LOS. Secondary outcome was change in HRQL, assessed using PedsQL SCD Pain and Hurt and Pain Impact Domains measured in ED and at discharge. Independent variables were (1) time to first IV opioid, (2) total initial opioid dose (mg/kg/hr of morphine equivalents administered between ED and first study drug), and (3) Time to first oral opioid. Spearman correlations determined the associations with LOS. Using two‐sample t ‐tests, we compared mean change in HRQL scores between IV opioid initiated within 60 and >60 min, opioid doses in the highest and lowest tertiles, and oral opioid initiated within 24 and >24 hr. Two hundred and four patients participated at 8 sites. Mean (SD) age was 13.6 (4.7) years. Earlier initiation of oral opioids was strongly correlated with shorter LOS ( r = 0.61, P < 0.01). Higher initial opioid dose was weakly correlated with longer LOS ( r = 0.34, P < 0.01). Higher initial opioid doses (6 vs −2.2; P = 0.01) and oral opioids initiated within 24 hr (5.7 vs −1.7, P = 0.04) were associated with larger mean change in HRQL at discharge. Prospective trials evaluating the impact of ED care on outcomes of pain hospitalizations could improve SCD pain treatment. Am. J. Hematol. 91:1175–1180, 2016. © 2016 Wiley Periodicals, Inc.